National population prevalence of antibodies to SARS-CoV-2 in Scotland during the first and second waves of the COVID-19 pandemic. (September 2021) - Palmateer, N.E.; Dickson, E.; Furrie, E.; Godber, I.; Goldberg, D.J.; Gousias, P.; Jarvis, L.; Mathie, L.; Mavin, S.; McMenamin, J.; McNeilly, T.N.; Murcia, P.; et al.
Abstract: Objectives: Studies that measure the prevalence of antibodies to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ('seroprevalence') are essential to understand population exposure to SARS-CoV-2 among symptomatic and asymptomatic individuals. We aimed to measure seroprevalence in the Scottish population over the course of the COVID-19 pandemic – from before the first recorded case in Scotland through to the second pandemic wave. Study design: The study design of this study is serial cross sectional. Methods: We tested 41, 477 residual samples retrieved from primary and antenatal care settings across Scotland for SARS-CoV-2 antibodies over a 12-month period from December 2019-December 2020 (before rollout of COVID-19 vaccination). Five-weekly rolling seroprevalence estimates were adjusted for the sensitivity and specificity of the assays and weighted to reference populations. Temporal trends in seroprevalence estimates and weekly SARS-CoV-2 notifications were compared. Results: Five-weekly rolling seroprevalence rates were 0% until the end of March, when they increased contemporaneously with the first pandemic wave. Seroprevalence rates remained stable through the summer (range: 3%–5%) during a period of social restrictions, after which they increased concurrently with the second wave, reaching 9.6% (95% confidence interval [CI]: 8.4%–10.8%) in the week beginning 28th December in 2020. Seroprevalence rates were lower in rural vs. urban areas (adjusted odds ratio [AOR]: 0.70, 95% CI: 0.61–0.79) and among individuals aged 20–39 years and 60 years and older (AOR: 0.74, 95% CI: 0.64–0.86; AOR: 0.80, 95% CI: 0.69–0.91, respectively) relative to those aged 0–19 years. Conclusions: After two waves of the COVID-19 pandemic, less than one in ten individuals in the Scottish population had antibodies to SARS-CoV-2. Seroprevalence may underestimate the true population exposure as a result of waning antibodies among individuals who were infected early in the first wave.